Sistem Informasi Motor Vehicle Loan Submission Pada PT.Bank Central Asia Tbk - Giandari Maulani; Katri Olivia; M. Nizar Ayubi (UNIVERSITAS RAHARJA, 2021)
The Motor Vehicle Loan Submission Information System is a motor vehicle loan application system funded by PT. Bank Central Asia Tbk because of the current trend of people wanting to own a motor vehicle but not by purchasing cash, which in this case means purchasing on credit with assistance from the bank. In the system of purchasing goods on credit, customers are generally required to pay a down payment, then the rest of the price of the goods is paid in installments over a certain period. The credit system at dealers is an alternative that is widely chosen, especially for financing Motor Vehicle Loans (KKB). In this study, the SWOT analysis method (Strengths, Weaknesses, Opportunities and Threats) is used with the aim of knowing what data are input and output on the running system. With this system, it can make it easier for customers to perform simulations and find out the installments to be paid. The result of this research is a Motor Vehicle Loan Submission Information System at PT. Bank Central Asia Tbk.